MANAJEMEN PEMBIAYAAN PENDIDIKAN UNTUK MENINGKATKAN MUTU PENDIDIKAN DI SMP Negeri 24 BANDAR LAMPUNG - Sri Indarti; Kosmalinda; Evi Sayyidah (UNISAN JURNAL, 2022)
One way to improve the quality of education is to pay attention to the national education standards that apply in Indonesia, including financing standards. Available school finances need to be managed using the management function so that financing management can be carried out effectively and efficiently. Functions in financing management include planning, bookkeeping, use of finance or spending, recording, monitoring, and accountability. Education financing management is one of the keys to the successful implementation of teaching and learning activities in schools because the cost of education has a linear correlation with the quality of education.